Maps of degree one, LS category and higher topological complexities - Rudyak, Yuli B.; Sarkar, Soumen (Topological Methods in Nonlinear Analysis, 2023)
In this paper, we study the relation between the Lusternik-Schnirelmann categoryand the topological complexity of two closed oriented manifolds connected by a degree one map.